Proceedings of the First Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2018
DOI: 10.2991/piceeba-18.2018.59
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work-Family Conflict on Turnover Intention of Banksr Employees in Padang with Burnout as The Mediating Variable

Abstract: The study aims to examine the effect of work-family conflict on turnover intention of banks' employees in Padang with burnout as the mediating variable. The population of this study was all female employees at 7 conventional banks selected in the city, and the population number was 378 people. The sampling technique of this research was purposive sampling technique and the sample size was 100 people. The primary data were analyzed using regression analysis technique with a mediating variable and a causal step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…In accordance with the previous statement, another research conducted by Li, Sawhney and Tortorella (2019) also found that work-family conflict is a significant predictor for employees' turnover intention and have a significant positive correlation. Additionally, in one of the researches done in one of the banks in Indonesia deduced that work-family conflict does indeed have a direct, significant and positive impact on turnover intention of the bank employees (Sarianti, Fitria, & Engriani, 2018). On the contrary, Pradana and Salehudin (2015) found that work-life conflict is shown to have no influence towards turnover intention.…”
Section: Work-family Conflictmentioning
confidence: 98%
“…In accordance with the previous statement, another research conducted by Li, Sawhney and Tortorella (2019) also found that work-family conflict is a significant predictor for employees' turnover intention and have a significant positive correlation. Additionally, in one of the researches done in one of the banks in Indonesia deduced that work-family conflict does indeed have a direct, significant and positive impact on turnover intention of the bank employees (Sarianti, Fitria, & Engriani, 2018). On the contrary, Pradana and Salehudin (2015) found that work-life conflict is shown to have no influence towards turnover intention.…”
Section: Work-family Conflictmentioning
confidence: 98%
“…Hasil penelitian ini selain mampu dijelaskan dengan teori yang ada, secara empiris juga didukung oleh beberapa penelitian yang telah dilakukan sperti Nafisah, (2019) menjelaskan bahwa burnout mampu dalam memperkuat adanya hubungan yang terjadi antara work-family conflict terhadap turnover intention. Penelitian yang dilakukan oleh Sarianti et al, (2018) menemukan hasil "Burnout is proven as a significant mediating variable of Work-Family Conflict with Turnover intention".…”
Section: Tabel 5 Hasil Uji Heterokidasitasunclassified